Hair analysis for opiates: evaluation of washing and incubation procedures - BALIKOVA, M. A; HABRDOVA, V (Journal of chromatography. B, 2003)
Hair analysis of drugs of abuse has been a subject of interest from a clinical, social and forensic perspective for years because of the broad time detection window after intake in comparison to urine or blood. However, the correct and reliable interpretation of opiates findings in an authentic hair sample requires optimalisation and standardisation of decontamination and incubation procedures. Comparing various published methods, we have found some variability in them and no unequivocal recommended procedure for starting with a method directly. Therefore, various combinations of solvents, of various polarity, as washing solvents were tested for removing opiates from the external surface of real hair samples. The yields of opiates from these washings were compared with the yields from the interior of the hair matrix after digestion with various procedures. The opiates after digestion were cleaned up from resulting solution on extraction columns with mixed solid-phase and analysed by GC–MS in standard EI mode after silylation. The efficiencies of neutral (Söerensen buffer, pH 7.4), acid (0.1 M HCl) and basic (1 M NaOH) digestion of the hair matrix were evaluated and the relative recoveries for morphine, codeine, dihydrocodeine and hydrocodone were compared. As it is very problematic to imitate the reference hair sample with a specific amount of analytes incorporated inside, which can be used for calibration to get a close estimate of the quantities of analytes inside the solid authentic sample, the total digestion of a hair sample in basic medium was considered to be a very important reference basis for quantitative determinations. The ratios of hydrolysis of labile 6-acetylmorphine or acetylcodeine were tested and evaluated in practical routine conditions of acid or neutral digestion of hair. Comparing the three methods of incubation of authentic hair samples, the methods using 1 M NaOH or 0.1 M HCl yielded higher recoveries of total equivalents of morphine or codeine, whereas the incubation in Söerensen buffer allowed the reflection of real ratios of labile metabolites and/or parent compounds in an original sample. This method has been shown to be capable of detecting hydrocodone in hair with other opiates concomitantly and to indicate the drug abuse pattern of a person at various time intervals in the past.